The Outdoor Field Test and Energy Yield Model of the Four-Terminal on Si Tandem PV Module - Kenji Araki; Hiroki Tawa; Hiromu Saiki; Yasuyuki Ota; Kensuke Nishioka; Masafumi Yamaguchi (Applied Sciences, 2020)
The outdoor field test of the 4-terminal on Si tandem photovoltaic module (specifically, InGaP/GaAs on Si) was investigated and a performance model, considering spectrum change affected by fluctuation of atmospheric parameters, was developed and validated. The 4-terminal on Si tandem photovoltaic module had about 40% advantage in seasonal performance loss compared with standard InGaP/GaAs/InGaAs 2-terminal tandem photovoltaic module. This advantage increases (subarctic zone < temperate zone < subtropical zone). The developed and validated model used an all-climate spectrum model and considered fluctuation of atmospheric parameters. It can be applied every type of on-Si tandem solar cells.